Effects of Cochlear Implants on the Quality of Life of Children - Namra Rasheed, Kousar Parveen, Muhammad Aqeel Ahmed (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: The purpose of this study is to determine the effectiveness of cochlear implants also examining the factors influencing the quality of life of children after CI. Study Design: Cross-sectional Place and Duration: PHFMC(BHU 189,Toba Tek Singh). Jan 2020-Oct 2020 Methods: Forty five children of aged between 3-10 years were presented in this study. Patients had cochlear implantation were included. Informed written consent was taken from the parents of children for demographically details in which age, sex, parent’s education status, residency and employment. Paediatric Quality of Life Inventory 4.0 - Generic core scale (PedsQLTM 4.0 - GCS) was used. Children were assessed in terms of communication, self-reliance, socio economic behavior, education, family understanding and effects of implantation. SPSS 23.0 version was used to analyze data. Results: Among 45 cases, majority of the patients 27 (60%) were males and 18 (40%) were females. 6.07±3.32 years were the mean age of the children. 24 (53.3%) cases were from urban areas and 19 (46.7%) patients had rural residency. Majority of the mothers 29 (64.4%) were housewives and 21 (46.7%) mothers were literate. Mean age at the time of surgery was 4.12±3.63 years. Mean time of cochlear implantation 4.01±1.21 years. We found that the improvement in communication with the known people was 23 (51.1%) and before cochlear implantation effectiveness of hearing aids were slightly low 11 (24.4%). We found that the improvement of social relationships, family well-being, within-family relationships, educational conditions, and self-reliance were all observed to be satisfactory. Conclusion: In this research we concluded that the cochlear implantation was significantly helpful for children in hearing, language understanding, self-reliance, educational conditions. An understanding of the child’s and family’s unique needs will aid in the development of personalized speech therapy, which can help enhance outcomes for rehabilitation.